Left and Right Ventricle Functions in Patients Obstructive Sleep Apnea and Their Relationship with Apelin Levels. Issue 4 (October 2015) - Çil, Cem; Karabağ, Turgut; Tekin, İshak Özel and Sayın, Muhammet Raşit and Güdül, Naile Eriş and Altun, Remzi and Aydın, Mustafa
No abstract available